SuperNova : super-peers based architecture for decentralized online social networks - Sharma, Rajesh (2013)
Recent years have seen several earnest initiatives from both academic researchers as well as open source communities to implement and deploy decentralized online social networks (DOSNs). The primary motivations for DOSNs are privacy and autonomy from big brotherly service providers. However decentralization introduces many challenges. One of the principal problems is to guarantee availability of data even when the data owner is not online, so that others can access the said data even when a node is offline or down. Intuitively this can be solved by replicating the data on other users' machines. Existing DOSN proposals try to solve this problem using heuristics which are agnostic to the various kinds of heterogeneity both in terms of end user resources as well as end user behaviors in such a system. In this paper, we argue that a pragmatic design needs to explicitly allow for and leverage on system heterogeneity, and provide incentives for the resource rich participants in the system to contribute such resources. To that end we introduce SuperNova - a super-peer based DOSN architecture. Super-peers can help (i) bootstrap new peers who are yet to have/find any friends by either providing them storage space, (ii) maintaining a directory of users, so that users can find friends in the network by name or interests, (iii) help peers find other peers to store their content in case they don't have adequate friends to do so, or if their friends are already overloaded. Users may want to become super-peers out of altruism (they want DOSNs to succeed), for the sake of the reputation (e.g., being an influential member for an interest based community) as well as potentially to monetize their special roles (e.g., run advertisements). While proposing the SuperNova architecture, we envision a dynamic system driven by incentives and reputation, however, investigation of such incentives and reputation, and its effect on determining peer behaviors is a subject of our future study. I- this paper we instead investigate the efficacy of a super-peer based system at any time point (a snap-shot of the envisioned dynamic system), that is to say, we try to quantify the performance of SuperNova system given any (fixed) mix of peer population and strategies.